Hardness of denture base and hard chair-side reline acrylic resins Dureza de resinas acrílicas para base de prótese e reembasamento imediato - Andrea Azevedo; Ana Lucia Machado; Carlos Eduardo Vergani; Eunice Teresinha Giampaolo; Ana Cláudia Pavarina (University of São Paulo, 2005)
INTRODUCTION: The hardness of denture base materials may undergo changes due to continued polymerization reaction and water uptake. However, the extent to which these processes affect the hardness of materials is still unclear. OBJECTIVE: In this study, the degree of conversion of two hard chair-side reline resins (Duraliner II-D and Kooliner-K) and one heat-cured acrylic resin (Lucitone 550-L) was evaluated indirectly by measuring the surface hardness. The effect of immersion in water on this property was also analyzed. MATERIALS AND METHODS: After processing following the manufacturers' instructions, specimens (5mm diameter and 2mm thickness) were dry stored at room temperature and the Vickers hardness (VHN) was measured with a hardness tester after 0, 2, 7, 30 and 90 days. Specimens were then immersed in water at 37ºC and hardness was evaluated after the same time intervals. Five specimens were prepared for each material. Data were analyzed by Kruskal-Wallis test (P=.01). RESULTS: When dry stored, material L showed an increase in hardness (P<.01) from 0-day (VHN=23.2) to 30-day (VHN=27.1), after which no significant change was observed. A continuous increase in hardness was observed for material D from 0-day (VHN=4.6) to 90-day dry storage (VHN=7.3). For material K, an increase in hardness was observed up to 7-day (VHN=9.2), and then leveled off (P>.01). After 2-day water storage, all materials showed a significant reduction in hardness (P<.01). CONCLUSION: In general, the hardness of the materials evaluated increased during dry storage and decreased after immersion in water. INTRODUÇÃO: A dureza das resinas para base de prótese e para reembasamento imediato pode apresentar alterações devido à polimerização continuada e absorção de água. Entretanto, a magnitude do efeito de cada um desses processos ainda não foi definida. OBJETIVO: Neste estudo, o grau de conversão de duas resinas autopolimerizáveis para reembasamento (Duraliner II-D and Kooliner-K) e de uma resina termopolimerizável para base de prótese (Lucitone 550-L) foi avaliado, indiretamente, por meio da mensuração da dureza. O efeito da imersão em água sobre essa propriedade também foi analisado. MATERIAL E MÉTODOS: Após a polimerização, amostras (diâmetro - 5 mm; espessura - 2 mm) foram armazenadas a seco em temperatura ambiente e a dureza Vickers (VHN) foi mensurada após 0, 2, 7, 30 e 90 dias. As amostras foram, então, imersas em água a 37º C e a dureza foi avaliada nos períodos citados. Cinco amostras foram preparadas para cada material. Os resultados foram analisados utilizando-se o teste de Kruskal-Wallis (P=.01). RESULTADOS: Para o armazenamento a seco, o material L apresentou aumento significativo na dureza (P<.01) de 0 (VHN=23.2) para 30 dias (VHN=27.1), após o qual nenhuma diferença significativa foi observada. Aumento contínuo na dureza foi observado para o material D de 0 (VHN=4.6) para 90-dias (VHN=7.3). Para o material K, aumento na dureza foi observado até 7 dias (VHN=9.2) quando ocorreu a estabilização (P>.01). Após 2 dias de armazenamento em água, todos os materiais apresentaram redução significativa na dureza (P<.01). CONCLUSÕES: A dureza dos materiais avaliados aumentou durante o armazenamento a seco e diminuiu após a imersão em água.